2021
DOI: 10.3390/molecules26144285
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Comparison of Melatonin and Its Bromobenzoylamide Derivatives in Lipopolysaccharide (LPS)-Induced RAW 264.7 Cells and Croton Oil-Induced Mice Ear Edema

Abstract: The pineal gland is a neuroendocrine organ that plays an important role in anti-inflammation through the hormone melatonin. The anti-inflammatory effects of melatonin and its derivatives have been reported in both in vitro and in vivo models. Our previous study reported the potent antioxidant and neuroprotective activities of bromobenzoylamide substituted melatonin. In silico analysis successfully predicted that melatonin bromobenzoylamid derivatives were protected from metabolism by CYP2A1, which is a key enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…It is also associated with growth hormone secretion in children [ 11 ]. Additionally, melatonin regulates energy metabolism and the immune system [ 12 ] and possesses various biological activities, such as anti-inflammatory [ 13 ], antioxidant [ 14 ], and neuroprotective [ 15 ] activity. The nocturnal plasma level of melatonin increases to reach a maximum at the age of 1–3 years.…”
Section: Introductionmentioning
confidence: 99%
“…It is also associated with growth hormone secretion in children [ 11 ]. Additionally, melatonin regulates energy metabolism and the immune system [ 12 ] and possesses various biological activities, such as anti-inflammatory [ 13 ], antioxidant [ 14 ], and neuroprotective [ 15 ] activity. The nocturnal plasma level of melatonin increases to reach a maximum at the age of 1–3 years.…”
Section: Introductionmentioning
confidence: 99%
“…Negative controls (cells without H 2 O 2 treatment) were considered as 100% protection and H 2 O 2 -treated cells as 0% protection. Melatonin and rasagiline (Sigma-Aldrich Co. LLC, St. Louis, MO, USA) were used as references because of their potent antioxidant and neuroprotective effects, which were established by several in vitro and in vivo studies [ 17 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…The latter was extensively studied by this team in a novel pin+icvAβ 1-42 Alzheimer animal model, and its role as a direct free radical scavenger was unequivocally demonstrated in the prevention of oxidative stress and neurodegenerative features induced by that model [ 16 ]. IPA was able to prevent ROS damage and cell death caused by the addition of Aβ-peptide on SK-N-SH human neuroblastoma cells and primary rat hippocampal neurons [ 17 ]. IPA also demonstrated full protection against the death of primary neurons and SK-N-SH cells exposed to Aβ-mediated damage and DDTC-induced lipid peroxidation in PC12 cells [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…11 Therefore, key factors in ferroptosis-related pathways like SLC7A11, GPX4, ACSL4 and lysophosphatidylcholine acyltransferase 3 (LPCAT3) played an important role in multiple diseases including tissue injury, inflammation and IDD. 12 Melatonin (N-acetyl-5-methoxytryptamine, MLT), is an indoleamine hormone, which displays a variety of biological properties, including anti-oxidant, 13,14 anti-inflammatory, 15,16 antiapoptosis, 17,18 anti-cancer, 19 anti-diabetic 20 and immunomodulation. 21,22 Recently, clinical and animal studies suggested the role of MLT in the IDD.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin ( N ‐acetyl‐5‐methoxytryptamine, MLT), is an indoleamine hormone, which displays a variety of biological properties, including anti‐oxidant, 13,14 anti‐inflammatory, 15,16 anti‐apoptosis, 17,18 anti‐cancer, 19 anti‐diabetic 20 and immunomodulation 21,22 . Recently, clinical and animal studies suggested the role of MLT in the IDD 3,23–29 .…”
Section: Introductionmentioning
confidence: 99%